Overcoming the blood-brain barrier: targeted delivery strategies for gliomas - Du, Xue; Chen, Chunbao; Zeng, Yijun; Lin, Zhinei (Frontiers in Pharmacology, 2025)
Neurological gliomas, as the most common and deadly primary brain tumors, face two major therapeutic obstacles: the blockade of the blood-brain barrier (BBB) and high tumor heterogeneity. In recent years, research on novel drug delivery systems has brought hope for glioma treatment. This article elaborates on the research progress of novel drug delivery systems in glioma treatment, including various nanocarriers, targeted delivery strategies, and gene therapy drug delivery systems. It analyzes their advantages and challenges, outlooks future development directions, and aims to provide a reference for optimizing drug delivery systems for glioma therapy.